Development of an analytical method to measure 17b-estradiol metabolite concentrations in MCF-7 and MCF-12A cell lines - Lottering, Mona-Liza (University of Pretoria, 2013)
Dissertation (MSc (Physiology))--University of Pretoria, 2007.